POLITICAL IMPLICATIONS OF PROMOTING CRITICAL THINKING THROUGH EDUCATIONAL GOVERNANCE MODERNIZATION ON CHINESE CULTURE - Wang Yi Tong, Nur Ajrun Binti Khalid (Chelonian Research Foundation, 2023)
This study aimed to investigate the political implications of educational governance modernization on Chinese culture. The purpose of the study was to examine how changes in educational governance have affected various aspects of Chinese culture, including nationalism, patriotic education, ideological control, political socialization, social stability, and the promotion of Chinese culture globally. The study employed a methodology that involved conducting a comprehensive search of online databases, academic publications, and relevant archives to identify scholarly papers. The results of the study revealed significant findings regarding the political implications of educational governance modernization on Chinese culture. Education played a crucial role in fostering nationalism and nurturing patriotic sentiments among Chinese individuals. The reforms in educational governance aimed to instill a sense of national pride, unity, and loyalty to the government among students. The study also highlighted the importance of social stability and harmony in educational governance modernization. While efforts were made to establish societal order favorable to economic growth and political stability, concerns were raised regarding the balance between conformity and individualism and the potential impact on critical thinking and innovation. Based on the findings, recommendations Chinese officials should strive to strike a balance between encouraging patriotism and fostering the development of critical thinking skills in schools. Creating an environment conducive to the free exchange of ideas and respect for alternative viewpoints was deemed essential. Keywords: Political Implications, Educational Governance, Modernization, Chinese, Culture